2017
DOI: 10.3892/ol.2017.7251
|View full text |Cite
|
Sign up to set email alerts
|

No association between triple‑negative breast cancer and prognosis of patients receiving breast‑conserving treatment

Abstract: The role of triple-negative breast cancer (TNBC) in breast-conserving treatment is controversial. The present study aimed at evaluating the prognosis of patients with TNBC following breast-conserving treatment (BCT) within 5 years. The present study investigated a cohort of 757 patients with early stage breast cancer, diagnosed and treated with BCT between January 2002 and March 2010 at Tianjin Medical University Cancer Institute and Hospital. The patients were divided into three groups according to receptor e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Among our patients, 96.9% were administered chemotherapy, including 54.9% administered neoadjuvant chemotherapy as a result of advanced stage or poor prognosis. Neoadjuvant chemotherapy was not beneficial to PABC patient survival in our study, but it improved the rate of BCS (22.5%) in PABC compared to approximately 10% in non‐PABC patients in China . As all patients who received chemotherapy were in postpartum, we could not evaluate the effect of chemotherapeutics on the pregnancy and fetus, but most of the previous literature has shown that chemotherapy can be safely used during the second and third trimesters .…”
Section: Discussionmentioning
confidence: 99%
“…Among our patients, 96.9% were administered chemotherapy, including 54.9% administered neoadjuvant chemotherapy as a result of advanced stage or poor prognosis. Neoadjuvant chemotherapy was not beneficial to PABC patient survival in our study, but it improved the rate of BCS (22.5%) in PABC compared to approximately 10% in non‐PABC patients in China . As all patients who received chemotherapy were in postpartum, we could not evaluate the effect of chemotherapeutics on the pregnancy and fetus, but most of the previous literature has shown that chemotherapy can be safely used during the second and third trimesters .…”
Section: Discussionmentioning
confidence: 99%
“…Study of Mu et al on 20-80 years population with early stage cancer showed the average age of 45 years. 10 In the United States, breast cancer were mostly found in average of 40-70 years, with tumor size of 2 to 4.9 cm at the first diagnosis. 11 While as in United Kingdom, the first diagnosed is at 60-70 years, with tumor size of 2 to 5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…It was even found that BCT had a survival benefit for TNBC compared with total mastectomy ( 25 ). This might be due to the fact that most reviews and observational studies focused on the prognostic impact of BCT for TNBC versus other molecular subtypes of breast cancer, and therefore only included patients who received BCT ( 2 , 20 , 26 , 27 ); whereas other studies looked at the effect of different surgical interventions on prognosis and included patients who had undergone total mastectomy ( 18 , 25 ). Therefore, it is the current consensus that TNBC is not contraindicated to BCT ( 21 ).…”
Section: Introductionmentioning
confidence: 99%